Pengaruh Kualitas Pelayanan Dalam Pembiayaan Murabahah Terhadap Kepuasan Nasabah - Anshoriyah Rohman (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2017)
The success and failure of a bank is determined by how the bank can provide satisfaction to its customers. There are several concept to built customer satisfication, among others, the concept of marketing, the concept of quality, the concept of service quality and so forth. Various attempts by banking companies to survive after of this prolonged crisis in the face of intense competition with other banking companies. Customer satisfication of the customer is the most important form of service for every banking, because with the satisfication of the customer we can know the evaluation of all products offered to the customer. One of the product offered is murabahah financing which is often used by customers in every banking. The result of the research at Bank Muamalat Branch Sragen is murabahah banking sevice in Bank Muamalat Branch Sragen in accordance with Islamic Shari’a and the influence of murabahah financing services to customer satisfication in Bank Muamalat Branch Sragen.